Analisis Produksi Program Kabar Misteri Jakarta Televisi (JAKTV) - Fadhil Muhammad Tanjung; Mulkan Habibi (Institut Nalanda, 2024)
This research aims to analyze how the production process of the Kabar Misteri program is carried out, starting from the pre-production to post-production stages, using the Television Program Production Theory as an analytical framework. A qualitative approach method with descriptive research type is used to achieve this goal, by conducting literature studies and interviews as data sources. The results showed that the pre-production stage of the Kabar Misteri program involved three main steps, namely idea discovery, planning, and preparation. Furthermore, in the production stage, the program follows the production plan that has been prepared, with good production teamwork and a smooth shooting or video process. In the post-production stage, several steps are followed, including offline editing, online editing, and mixing. This process usually takes three days to complete one episode, which consists of four segments in a month.